2012
DOI: 10.28945/1548
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intent to Continue Using Online Learning: A Tale of Two Universities

Abstract: This paper examines the determinants of intent to continue using online learning. The success of online learning programs depends not only on students' satisfaction but also their intent to continue using it. Unlike the recent research under this topic, its antecedent model consists of the following three components that affect learners' intent to continue using online learning: perceived social ability, online learning readiness, and perceived usefulness. Eight hundred and seventy-two samples collected from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Cross cultural comparisons and longitudinal studies need to be conducted in order to examine possible changes over time and cultural effects on the relative importance of determinants of eLearning usage. The finding of Brahmasrene & Lee (2012) that there is a significant difference between the U.S sample and the Korean sample regarding the perceived usefulness of online learning system adds weight to this. Also, the largest adopters of eLearning are corporations, which find it useful in keeping their workforce up to date.…”
Section: Future Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…Cross cultural comparisons and longitudinal studies need to be conducted in order to examine possible changes over time and cultural effects on the relative importance of determinants of eLearning usage. The finding of Brahmasrene & Lee (2012) that there is a significant difference between the U.S sample and the Korean sample regarding the perceived usefulness of online learning system adds weight to this. Also, the largest adopters of eLearning are corporations, which find it useful in keeping their workforce up to date.…”
Section: Future Researchmentioning
confidence: 91%
“…The success of online learning programs depends not only on students' satisfaction but also their intent to continue using it (Brahmasrene & Lee, 2012). Thus this study addresses the following four related research questions:…”
Section: Introductionmentioning
confidence: 99%
“…The IS literature suggests that continuance intention is a critical long‐term outcome and indicator of IS success (e.g., Bhattacherjee & Premkumar, ; Hu, Brown, Thong, Chan, & Tam, ). It is also regarded as the key to understanding how to retain users and sustain their participation, especially in online communities that largely depend on user contributions (e.g., Brahmasrene & Lee, ; Fang & Neufeld, ). Next, each hypothesis is discussed.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Similarly, in a virtual community context (i.e., online travel), Kim, Lee, and Hiemstra () indicated that a sense of belonging, which is a core component of SOC, has a significant impact on members' loyalty toward their community. In addition, Brahmasrene and Lee () showed in an online learning setting that SOC is a significant predictor of continuance intention. Taken together, these findings suggest that the more a user feels a SOC, the more he is likely to possess continuance intention.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…While research is beginning to examine the use of SNSs such as Facebook for educational endeavors (Brahmasrene & Lee, 2012;Buzzetto-More, 2012), the current research is focused purely on the entertainment, or hedonic use of these networks. However, the results can be generalized to other online systems in future studies if one looks at perceived usefulness rather than perceived playfulness as Bhattercherjee (2001) did.…”
Section: Limitations and Future Researchmentioning
confidence: 99%